What Would a Wise Woman Do? : Questions to Ask Along the Way - Levinson, Jay Conrad; Atchison, Laura Steward (Morgan James Publishing, 2012)
Whether stuck on autopilot or totally off course, What Would a Wise Woman Do? provides a roadmap for today's woman back to a more authentic and joyful life. Laura Atchison had it all-a great career, ambitious goals, and loving family-when she realized she was off course. By digging deeper, she discovered she hadn't been asking herself the right questions-and as a result, had been living the wrong answers. By revealing her riveting and candid story--including mistakes she made along the way--Atchison provides practical lessons on how to be a more wise and fulfilled woman by asking the right key questions in career, family, relationships, spiritual life, finances, and more.